Gaya Komunikasi Komunitas BRIC Esports dalam Upaya Meningkatkan Efektivitas Strategi Dalam Bermain Mobile Legends - Hamdani, Ade Ilham (CV. ITTC INDONESIA, 2024)
The development of online games itself cannot be separated from the development of computer technology and computer networks themselves. Mobile Legends: Bang Bang is a type of Multiplayer Online Battle Arena (MOBA) game that features 5 vs 5 battles, classic 3 lane battles. The method used in this research uses a qualitative approach as a method or way to achieve research objectives. This research uses a data analysis method that includes reduction and interpretation. Researchers collected data in the field by writing down findings into small notes on observations made and transcribing the results of interviews that have been obtained. This research explains how the BRIC Esports community's communication style in an effort to increase the effectiveness of strategies in playing Mobile Legends. This research is useful to be a reference and information for other communities or organizations in order to be better at choosing communication styles, especially in efforts to increase the effectiveness of strategies in playing Mobile Legends. The results of this study indicate that the communication style of the BRIC Esports community in an effort to increase the effectiveness of strategies in playing Mobile Legends, namely equalitarian style, dynamic style, controlling style, structuring style, and relinguishing style.